An Analysis of Performance-critical Properties of Modelica Models. Issue 1 (2015) - Cafferkey, Neil; Provan, Gregory
Abstract: Equation based object-oriented modelling languages such as Modelica are increasingly used for modelling complex electro-mechanical systems. Although compiling and executing a Modelica model can in some cases take many days, the performance characteristics of Modelica models and compilers are not well understood. Through the study of the compiler component of a widely used open-source Modelica implementation, OpenModelica, and a set of representative electronic models, we measure how various model properties influence the time contributions of different compilation-simulation phases. Wide differences in running times are observed. We highlight the factors contributing to these differences and put forward some strategies for improving future performance.